Охоронні дослідження багатошарового поселення у с. Розваж на Рівненщині - Позіховський, О.Л.; Бардецький, А.І. (Археологічні дослідження в Україні, 2009)
The materials of a dwelling and household complex of Malytska culture from a multilayer settlement in Rozvazh village of Rivne region, studied for the first time at the eastern territory of this culture, are presented to the scientific circulation. The material of the 1st millennia BC found in the cultural layer and in objects has been analysed.